Applications of 3D printing in pediatric dentistry: a literature review - Basim, Marwa; Al-Khatib, Ali Rajih; Rajion, Zainul Ahmad (College of Dentistry, University of Mosul, 2024)
Many challenges may occur during the dental intervention of pediatric patients. One of the steps to overcome these challenges is shifting towards 3D technology to obtain superior and precise performance. Among these advancements, the applications of 3D printing concepts have recently emerged. Dental professionals and patients may get many benefits from the use of 3D printing technology. This review will help the researchers and clinicians to consider the applications, benefits as well as constraints of this modern digital technology for efficient implementation of their procedures in pediatric dental practice